Development of a conceptual model of stable and satisfactory marriage in couples applying for adoption: a qualitative study - Nazemi, Maryam; Amiri Majd, Mojtaba; Ghamari, Mohammad; Asadi, Masoud (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was aimed to develop a conceptual model of satisfactory sustainable marriage in couples seeking adoption. Method: This research has been done qualitatively using grounded theory of the foundation. Using purposive sampling method, the subjects were selected according to the inclusion criteria and until theoretical saturation, finally 18 couples with satisfied and stable marriages a semi-structured interview was conducted for them and analyzed using Strauss and Corbin continuous comparison method. Results: The product of the open coding stage was reaching 112 primary codes, 23 sub-categories and 9 main categories and one central category. The central category in this study is infertility acceptance, a dynamic for the experience of genuine and committed love during marriage. Community, strategic support of those relatives the interventionist conditions and the category of personality and educational structure of couples Background and couples used constructive strategies to resolve marital and family conflicts and religious confrontation as constructive strategies and the end result of life satisfaction, acceptance with compassion and commitment to the spouse. Conclusion: Based on the results of this study, infertility acceptance and the experience of genuine and committed love in infertile couples whose main outcome is satisfaction is not accidental but is possible by constructive and active choice and action and is an individual, family and interactive process that Couples consciously strive for the growth and excellence of marriage and care for it, companionship, marital union and the acquisition of marital skills and effective strategies for health and happiness, and ultimately gain satisfaction and stability in marriage.